GAMBARAN TINGKAT STRESS AKIBAT HOSPITALISASI PADA BALITA DI RUANG GOLEK RSUD KABUAPATEN INDRAMAYU - Titin Hidayatin (JURNAL KESEHATAN INDRA HUSADA, 2022)
For children, hospitalization is an experience that is threatening, scary, lonely and confusing so that children can experience stress. Hospitalization stress is a form of individual stressor that lasts as long as the child is hospitalized. The purpose of this study is to find out the description of the stress level due to hospitalization in toddlers in the Golek Room of the Indramayu District Hospital in 2018. The research method used is descriptive. The research population is toddlers who are hospitalized in the golek room. A sample of 58 respondents was taken using a consecutive sampling technique. The instrument used is a questionnaire sheet about hospitalization stress. The data analysis design used was univariate. The results showed that 30 toddlers (51.7%) experienced stress due to hospitalization in the category of severe stress. A total of 41 children under five (70.7%) aged ≤ 2 years, as many as 34 toddlers (58.6%) were male, as many as 53 toddlers (91.4%) hospitalized for ≤ 3 days and as many as 38% toddlers (65, 5%) no history of previous hospitalization. The conclusion of this study is that toddlers have stress due to hospitalization in the category of severe stress. It is recommended that health workers and parents pay more attention to the impact of stress on children undergoing hospitalization and better understand its handling.